Pengaruh Pemberian Ekstrak Etanol Daun Kenikir (Cosmos Caudatus (L.) H.B.K.) Terhadap Volume Urin Tikus - Dewi, Anggita Oktaviani; , Nurcahyanti W.,M.Biomed.,Apt (2017)
Kenikir leaves (Cosmos caudatus (L.) H.B.K.) contain various chemical compounds such as quercetin which is known have diuretic effect. Quercetin have semi polar characteristic so it can extracted by ethanol. This study aims to determine the diuretic effect of ethanol extract of kenikir leaves. Thirty rats divided to 6 group namely group I normal control (CMC Na 0,5%), group II urea 1000mg/kgBW, group III furosemide 20mg /kgBW, group IV, V and VI are kenikir leaves ethanol extract dosage 500mg / kgBW, 1000mg /kgBW and 2000mg/kgBW. After treatment of all the test animals added 0.9% NaCl 50ml/kgBW, then each test animals put in metabolic cages and urine volume was measured on a cumulative 1-5 hours and 24 hours to calculate AUC1-5 AUC1-24 and Lipschitz value. AUC value analyzed by Analysis of Variance and Least Significant Difference test with credibility level 95%. The rasult of this study indicate AUC1-5 value ethanol extract of kenikir leaves dose of 500mg/kgBW can not increase urine volume, meanwhile dose of 1000mg/kgBW and 2000mg/kgBW are able to increase 47,27% and 114,62% urine volume of rats was significantly (p = 0.000) compared to normal controls. Lipschitz value each are 0,43, 0.58 and 0.88 so it do not have a diuretic effect.